The Role of Transformational Leadership in Enhancing Teacher Performance: A Qualitative Case Study in Indonesian Secondary Education - Nazaruddin Nazaruddin; Manap Somantri; Azizatul Khairi (Yayasan Sembilan Pemuda Indonesia, 2026)
This study explores how transformational leadership supports teacher performance at SMP Negeri 2 Muara Rupit, a public junior high school in South Sumatra, Indonesia. A qualitative case study design was used to examine leadership practices within their organizational and instructional context. Data were obtained from 16 purposively selected participants, comprising the principal, three vice principals, and twelve teachers, through semi-structured interviews, direct observations, and document analysis. The data were analyzed interactively through condensation, coding, thematic categorization, data display, and continuous verification. The findings show that the principal enacted four interconnected dimensions of transformational leadership. Idealized influence strengthened punctuality, responsibility, and instructional preparedness through consistent role modeling. Inspirational motivation increased teachers’ enthusiasm and commitment through vision communication, encouragement, and recognition. Intellectual stimulation supported pedagogical experimentation, technology integration, and collaborative professional learning through supervision and development activities. Individualized consideration increased teachers’ confidence and reflective practice through mentoring and constructive feedback. These practices were associated with a more disciplined, collaborative, and innovation-oriented work culture, although the pace of change varied among teachers. The study contributes a process-based explanation of how transformational leadership operates in a regional Indonesian school and highlights practical priorities for principal development, teacher mentoring, and school-based professional learning.